2013
DOI: 10.1002/pon.3308
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and defense mechanisms associated with treatment decisional preferences and quality of life in non‐metastatic breast cancer: a 1‐year prospective study

Abstract: Defense mechanisms are associated with treatment decisional preferences and interact with factors predicting HRQoL in women with breast cancer. Clinicians should address the patients' anxiety and depressive symptoms and refer patients with high repression tendencies for psychological evaluation and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 54 publications
5
31
0
6
Order By: Relevance
“…Trait anxiety predicted more depressive symptoms and poorer quality of life . In 2 studies, trait anxiety did not predict quality of life . Optimism predicted better quality of life, more positive affect, and lower levels of anxiety, depression, and psychological distress .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Trait anxiety predicted more depressive symptoms and poorer quality of life . In 2 studies, trait anxiety did not predict quality of life . Optimism predicted better quality of life, more positive affect, and lower levels of anxiety, depression, and psychological distress .…”
Section: Resultsmentioning
confidence: 91%
“…In 1 study, time since diagnosis predicted quality of life, with women being on average 4 years postdiagnosis presenting better quality of life . In 4 studies, however, no associations were found between time since diagnosis and psychological adjustment . Fatigue predicted more depressive symptoms, more anxiety, and worse quality of life while no association between fatigue and psychological adjustment was found in only 1 study .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Radiation treatment; applied after the diagnosis of breast cancer which is a severe and universal health problem of women, surgical procedures following the diagnosis and to prevent probable dissemination of the disease, includes a difficult and challenging period for both patient and family from physical, to psychological as well as social aspects; this negatively affects the life quality and comfort of the individual (Karakoyun-Celik et al, 2010;So et al, 2010;Ho et al, 2013;Hyphantis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of a tumor in the breast, fear of radiotherapy, the devices used and their effects are not known, perception of the waiting and treatment room, experiencing side effects and mutual occurrence of these factors causes anxiety. It has been determine in the literature that; anxiety due to radiotherapy is ranked first among other factors influencing patients' adherence to treatment, this is followed by physical discomfort (Dragomir and Fodoreanu, 2013;Ho et al, 2013;Hyphantis, 2013).…”
Section: Introductionmentioning
confidence: 99%